Study on Mechanical and Durability Properties of East Borneo Double Layer Porous Concrete Paving Block - Nor Fazilah Hashim; . Tumingan; Daru Purbaningtyas; Yudi Pranoto (Civil Engineering Journal, 2023)
Massive infrastructure development in East Borneo has reduced the water catchment area. One of the efforts to overcome this is by implementing porous paving with superplasticizer and local materials to improve quality, overcome material scarcity, and save costs. The purpose of this study was to determine the best layer variation of porous paving using Palu and Senoni materials with variations of 1/4, 1/2, and 3/4 of Senoni aggregate. In this study, the test object was made in the form of a beam with a quality of concrete planned at K300 MPa according to the compressive strength, flexural strength, porosity, and permeability values tested at the ages of 7, 14, 21, and 28 days. Based on the results, the variant layer of 1/4 Senoni obtained maximum compressive strength, flexural strength, porosity, and permeability of 17.306 MPa, 3.984 MPa, 18.120%, and 0.216 cm/second at the age of 28 days, respectively. Thus categorized this combination as C quality. Which was included in the C quality group with an application as a pedestrian area. According to the permeability result, double-layer porous paving can accelerate water absorption on the surface to prevent waterlogging when it rains. The increasing variation of layers in double-layer porous paving affects the compressive strength, flexural strength, porosity, and permeability. Doi: 10.28991/CEJ-SP2023-09-012 Full Text: PDF